P171 Zbtbs gene expression in CD4+ T cells and systemic pro-inflammatory cytokines in naïve and treated HIV patients. (14th July 2019) - Jimenez, Judith De Arcos; Briseño, Mariana Ruiz; Solano, Moises Ramos; Andrade-Villanueva, Jaime; Gonzalez-Hernandez, Luz; Sanchez-Reyes, Karina
Abstract : Background: Chronic inflammation in HIV infection has been associated with accelerated disease progression. Several external host factors contribute to inflammation like, microbial translocation and coinfections; as well as host intrinsic mechanisms; such as immune activation and the regulation of factors that participate in inflammation pathways. Members of the transcriptional factors ZBTB have been associated with repression of proinflammatory cytokines; the objective of this work was to identify if ZBTB repressors could be contributing to cytokines levels decrease in HIV+ ART-treated patients. Methods: CD4+ T cells were isolated from 12 HIV- and 21 HIV+, subclassified as naïve (n= 8) and treated (undetectable for ≥1 year, n=13). Gene expression of ZBTB2, ZBTB4, ZBTB7B, ZBTB17, ZBTB38, BCL6 and ZNF131 was determinate by qRT-PCR. Cytokine levels were quantified (IL-1β, IFN-α, IFN-γ, TNF-α, MCP-1, IL-6, IL-8, IL-10, IL-12, IL-17, IL-18, IL-23, IL-33) by flow cytometry in serum. Kruskal-Wallis test was used for statistical analysis. Results: In naïve patients, only ZBTB7B showed a significant up-regulation ( 2.76 fold). BCL6, ZBTB4, ZBTB38 had an increase but, were not significant (1.01, 0.91, 0.13 fold respectively); treated patients showed a significant up-regulation in ZBTB7B, ZBTB4 and ZBTB38 ( 2.23, 1.13, 1.04 fold respectively) and, BCL6 had 1.02 fold, however, it was no significant. ZBTB2, ZBTB17, ZNF131 did not have, all genes were compared to HIV negative subjects. No significant changes were observed in pro-inflammatory cytokines levels, however, in treated patients, IL-1β, TNF-α, IL-6, IL-10 and IL-12 showed lower levels compared with naïve patients. Conclusion: We showed an increase gene expression of some ZBTBs in HIV+ patients compared with healthy donors, these genes have been related to the inflammatory cytokines suppression; we found that this difference was higher in treated patients compared to naïve patients, this could be related to a decrease in TNF-α, IL-6, IL-10 and IL-12 systemic levels. Disclosure: No significant relationships.